Macroeconomic determinants of contingent protection: The case of the European Union - Bettina Becker; Martin Theuringer (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2000)
Contingent Protection has grown to become an important trade restricting device. In the European Union, protection instruments like antidumping are used extensively. This paper analyses whether macroeconomic pressures may contribute to explain the variations in the intensity of antidumping protectionism in the EU. The empirical analysis uses count data models, applying various specification tests to derive the most appropriate specification. Our results suggest that the filing activity is inversely related to the macroeconomic conditions. Moreover, they confirm existing evidence for the US suggesting that domestic macroeconomic pressures are a more important determinant of contingent protection policy than external pressures.
Keywords: F13; F4; 330; Antidumping; Protection; Macroeconomic Conditions; Estimation of Count Data Models; Protektionismus; Antidumping; Außenhandelspolitik; EU-Staaten